2017
DOI: 10.1186/s13075-017-1377-y
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum biomarkers from a two-year multicentre trial are associated with treatment response on knee osteoarthritis cartilage loss as assessed by magnetic resonance imaging: an exploratory study

Abstract: BackgroundThere is an obvious need to identify biomarkers that could predict patient response to an osteoarthritis (OA) treatment. This post hoc study explored in a 2-year randomized controlled trial in patients with knee OA, the likelihood of some serum biomarkers to be associated with a better response to chondroitin sulfate in reducing cartilage volume loss.MethodsEight biomarkers were studied: hyaluronic acid (HA), C reactive protein (CRP), adipsin, leptin, N-terminal propeptide of collagen IIα (PIIANP), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
0
26
0
5
Order By: Relevance
“…Metalloproteinases zinc-dependent enzymes (MMPs) play a key role in extracellular matrix remodeling and cartilage metabolism in knee OA. Among the various isoforms of MMPs, MMP-3 plays an important role in cartilage degradation, and has been shown to be responsive to therapeutic agents in patients with various stages of OA [ 12 , 45 , 46 ]. On the other hand, MMP-8 has been implicated in the degradation of already compromised cartilage matrix, and a few clinical studies have examined its response to therapeutic agents, and revealed conflicting results [ 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metalloproteinases zinc-dependent enzymes (MMPs) play a key role in extracellular matrix remodeling and cartilage metabolism in knee OA. Among the various isoforms of MMPs, MMP-3 plays an important role in cartilage degradation, and has been shown to be responsive to therapeutic agents in patients with various stages of OA [ 12 , 45 , 46 ]. On the other hand, MMP-8 has been implicated in the degradation of already compromised cartilage matrix, and a few clinical studies have examined its response to therapeutic agents, and revealed conflicting results [ 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a post-hoc study explored in a 2-year RCT of KOA patients, some serum biomarkers were found to be associated with a better response to chondroitin sulfate (CS) in reducing cartilage volume loss. The results suggested a greater response to CS treatment on cartilage volume loss in KOA patients with low level of inflammation (HA, leptin and adipsin) and/or greater level of cartilage catabolism (PIIANP, CTX-I, MMP-1, MMP-3) 45 . In another study, serum biomarker phenotypes associated with the occurrence of all-cause TJR were retrospectively explored using data from a phase III trial of tanezumab 46 .…”
Section: Early and Late Assessment Of Intervention Efficacy And Undermentioning
confidence: 92%
“…Osteoarthritis (OA) is recognized by the degeneration of articular cartilage, changes in the subchondral bone, inactivity-related stiffness, and chronic pain [1]. OA constitutes one of the largest cost burdens to healthcare with pain being the dominant symptom and reason for clinical presentation [2].…”
Section: Introductionmentioning
confidence: 99%